Gaya Parenting dalam Perspektif Psikologi Agama: Analisis Pemikiran Zakiah Daradjat - Ahmad Muzaky Fawaid; Aliyah Rahmadini; Badiah Baldatun Thoyyibah; Yuminah Rohmatullah (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study investigates parenting patterns through the lens of religious psychology, focusing on the perspectives of Zakiah Daradjat, a prominent academic and psychologist from UIN Syarif Hidayatullah Jakarta. Employing a qualitative approach based on literature analysis, the research delves into Daradjat’s thoughts on parenting grounded in spiritual values. Her view emphasizes that parenting extends beyond the biological aspect of childbirth; it involves nurturing the child’s moral and religious character from an early age, even before birth. Key values such as love, responsibility, and early religious education are considered essential in fostering a child's emotional and psychological well-being. The integration of these principles is believed to create a balanced developmental path aligned with Islamic teachings. Ultimately, this paper contributes to broadening the concept of Islamic parenting in a way that meets children’s psychological and spiritual needs in contemporary society.